A predictive model of the effective tensile and compressive strengths of concrete considering porosity and pore size. (10th May 2018) - Li, Dongqi; Li, Zongli; Lv, Congcong; Zhang, Guohui; Yin, Yueming
Highlights: A predictive model of the effective tensile and compressive strengths is established. The distribution and influence of pore size are considered in the strength model. Rationality and accuracy of the proposed expressions are assessed. Porosity higher influences compressive strength than tensile strength. Tensile and compressive strengths decrease with increases in porosity and pore size. Abstract: Pores, voids correspond to inevitable products in the formation of concrete and significantly affect its macroscopic effective strength. A lot of researches show that both porosity and pore structure have significant influence on the concrete strength and differences exist with respect to those influences on the tensile and compressive strengths. In this paper, first, the relationships between the effective tensile and compressive strengths of concrete and porosity are expressed respectively from the proposed simplified center pore model. Second, in order to further consider the influence of the pore structure, the pore size is chosen as the representative index of pore structure and an influence function related to the pore size is proposed based on the correlation analysis. The total influence coefficient of pore size is obtained by combining the pore size distribution function and influence function. Taking the total influence coefficient into account in the relation between the effective strength and porosity, explicit formulae of porous concrete effective tensile and compressive strengths are finally deduced. Through comparing the present approach with a few classical analytical solutions and experimental observations, the results indicate the reliability and accuracy of the proposed approach and the derived equations are simple and convenient to use. Analysis and discussion suggest that the effect of porosity on the compressive strength of concrete exceeds that of the tensile strength and that the effective concrete strength with the same porosity can be improved by decreasing the pore size.